Construction and validation of a hybrid model to measure perceived public service quality (PSQ) - Guenoun, Marcel; Chandon, Jean Louis; Goudarzi, Kiane (2016)
Today, public organizations make extensive use of marketing methods and concepts to design, implement and assess the services they deliver to their beneficiaries. The quality of the services offered is at the heart of their concerns. Public sector marketing requires tools that are adapted to the specific characteristics of the context. The main contribution of this research is to propose the construction of a hybrid model to measure perceived public service quality (PSQ), mixing public and private dimensions. It is based on a quantitative study conducted on a sample of 760 inhabitants of the French town of Besancon. - Reproduced.
Keywords: Public administration